Yttrium lithium fluoride composite crystal and preparation method thereof
By using different polishing liquids and organic solutions in the preparation process of yttrium fluoride composite crystals, combined with direct bonding technology and thermal isostatic treatment, the problem of low interface strength and damage threshold of yttrium fluoride composite crystals in the prior art is solved, and higher interface strength and lower processing requirements are achieved.
Patent Information
- Application Number
- CN202411935787.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-26
AI Technical Summary
In the prior art, the interface strength per unit area of yttrium lithium fluoride composite crystals are low and the temperature, pressure and time requirements are high during thermal isostatic pressure treatment.
The bonding surface of the yttrium lithium fluoride crystal is polished by using different polishing liquids and after treatment in a specific organic solution, the yttrium lithium fluoride composite crystal is prepared by direct bonding technology and thermal isostatic pressure treatment.
The interface strength per unit area of yttrium lithium fluoride composite crystal is improved and the interface damage threshold is reduced, and the temperature, pressure and time required for thermal isostatic pressure treatment is reduced.
Smart Images

Figure CN119753852A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium yttrium fluoride crystal bonding, in particular to a lithium yttrium fluoride composite crystal and a preparation method thereof. Background Art
[0002] Lithium yttrium fluoride is an excellent laser matrix crystal material with good spectrum and laser performance, and can achieve laser output of multiple wavelengths from mid-infrared to visible light and ultraviolet light at room temperature. More specifically, lithium yttrium fluoride has the characteristics of anti-ultraviolet radiation and suitable for multi-doping. The doped lithium yttrium fluoride prepared by adding different activation ions can emit lasers of different wavelengths at room temperature. Due to its small nonlinear refractive index, it can be used as an oscillator and preamplifier working material for high-power and high-energy laser devices.
[0003] In order to change the performance of lithium yttrium fluoride crystals, it is sometimes necessary to bond two crystals to form a lithium yttrium fluoride composite crystal. Public document CN104099665B discloses a lithium yttrium fluoride composite crystal and a preparation method thereof. The lithium yttrium fluoride composite crystal is prepared by bonding a doped lithium yttrium fluoride crystal in the a-axis crystal direction with a lithium yttrium fluoride crystal in the c-axis crystal direction, thereby improving the output efficiency of the laser. When the inventor used the above preparation method to prepare the lithium yttrium fluoride composite crystal, he found that the interface strength per unit area (kg / cm 2 ) and interface damage threshold (J / cm 2 ) are relatively low. In addition, the preparation of lithium yttrium fluoride composite crystals by the above method has high requirements for temperature, pressure and processing time during hot isostatic pressing.
[0004] To this end, in response to the problems raised in the above background technology, the present invention provides a method for laser crystal bonding, which effectively improves the interface strength per unit area and the interface damage threshold between two bonded crystals, improves the bonding surface strength, and at the same time, the processing pressure, temperature and time of hot isostatic pressing are relatively low. Summary of the invention
[0005] The object of the present invention is to provide a lithium yttrium fluoride composite crystal and a preparation method thereof to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing lithium yttrium fluoride composite crystals comprises the following steps:
[0008] S1, polishing the bonding surface of the lithium yttrium fluoride crystal in the c-axis crystal direction with polishing liquid A, and polishing the bonding surface of the doped lithium yttrium fluoride crystal in the a-axis crystal direction with polishing liquid B;
[0009] S2, placing the bonding surface of the c-axis crystal of the yttrium fluoride lithium crystal after polishing in step S1 into a mixed solution of 3-hydroxypropyltriethoxysilane and ethanol for 1-3 hours, then repeatedly washing with an excess of organic solvent, and naturally drying to obtain a pre-treated c-axis crystal of yttrium fluoride lithium crystal; placing the bonding surface of the a-axis crystal of the doped yttrium fluoride lithium crystal in step S1 into a mixed solution of 11-carboxy undecyltriethoxysilane and ethanol for 2-5 hours, then repeatedly washing with an excess of organic solvent, and naturally drying to obtain a pre-treated a-axis crystal of doped yttrium fluoride lithium crystal;
[0010] S3, pre-bonding the pre-treated c-axis yttrium lithium fluoride crystal obtained in step S2 to the end of the pre-treated a-axis doped yttrium lithium fluoride crystal by direct bonding technology to obtain a first intermediate product;
[0011] S4, applying a pressure of 1-5 MPa in a direction perpendicular to the bonding surface to the first intermediate product obtained in step S3 for 2-10 hours to obtain a second intermediate product;
[0012] S5. The second intermediate product obtained in step S4 is subjected to hot isostatic pressing treatment, wherein the pressure of the hot isostatic pressing treatment is 2-60 MPa, the temperature is 250-450° C., and the time is 2-10 hours. After the hot isostatic pressing treatment, vacuum annealing is performed, and the pressure of the vacuum annealing is 0.001-10 Pa, the time is 2-32 hours, and the temperature is 300-500° C. to obtain lithium yttrium fluoride composite crystals.
[0013] Furthermore, the a-axis doped lithium yttrium fluoride crystal is doped with a rare earth element, and the rare earth element is selected from at least one of thulium, holmium, erbium and praseodymium.
[0014] Furthermore, the components of the polishing liquid A in step S1 include hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water, and the mass ratio of hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water is 1:(2-3):(4-10):(40-80).
[0015] Furthermore, the components of the polishing liquid B in step S1 include sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, deionized water and nano vermiculite, and the mass ratio of sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, nano vermiculite and deionized water is 1:(3-6):(2-5):(7-12):(80-110).
[0016] Furthermore, in step S1, the smoothness of the c-axis lithium yttrium fluoride crystal and the a-axis doped lithium yttrium fluoride crystal after polishing both reaches 10 / 5, and the roughness of the lithium yttrium fluoride crystal and the doped lithium yttrium fluoride crystal after polishing is not greater than 0.8 nm.
[0017] Furthermore, the organic solvent in step S2 is a mixture of ethanol and acetone, and the mass ratio of acetone to ethanol is 1:(2-5).
[0018] Furthermore, in step S2, the mass ratio between 3-hydroxypropyltriethoxysilane and ethanol is 1:(20-45).
[0019] Furthermore, in step S2, the mass ratio between 11-carboxyundecyltriethoxysilane and ethanol is 1:(25-40).
[0020] A lithium yttrium fluoride crystal is prepared by the above-mentioned method for preparing the lithium yttrium fluoride composite crystal.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] Compared with the prior art, the present invention polishes the bonding surfaces of two crystals respectively by two different polishing liquids, and simultaneously treats the bonding surfaces of the two polished crystals by different organic solutions, thereby improving the van der Waals force between the two pieces of lithium yttrium fluoride, strengthening the strength of the bonding surfaces of the bonded crystals, and improving the interface strength per unit area and the interface damage threshold. At the same time, the temperature and pressure required for treating the bonded crystals in the present invention are relatively low. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The process flow chart of preparing lithium yttrium fluoride composite crystals of the present invention;
[0024] Figure 2 It is a schematic diagram of bonding between lithium yttrium fluoride crystal and doped lithium yttrium fluoride crystal in the present invention.
[0025] In the figure: 1. Lithium yttrium fluoride crystal with c-axis crystal orientation; 2. Doped lithium yttrium fluoride crystal with a-axis crystal orientation. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] See also Figure 1-2 , the present invention provides a technical solution:
[0028] Example 1
[0029] The preparation method of lithium yttrium fluoride composite crystal comprises the following steps:
[0030] S1, polishing the bonding surface of the lithium yttrium fluoride crystal in the c-axis crystal direction with a polishing solution A, wherein the components of the polishing solution A include hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water, and the mass ratio of hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water is 1:2.5:8:60;
[0031] Polishing the bonding surface of the a-axis doped lithium yttrium fluoride crystal with a polishing solution B, wherein the a-axis doped lithium yttrium fluoride crystal is doped with 3at% thulium, and the components of the polishing solution B include sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, deionized water and nano vermiculite, and the mass ratio of the sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, nano vermiculite and deionized water is 1:4:4:11:95;
[0032] The smoothness of the c-axis lithium yttrium fluoride crystal and the a-axis doped lithium yttrium fluoride crystal after polishing reached 10 / 5, and the roughness of the lithium yttrium fluoride crystal and the doped lithium yttrium fluoride crystal after polishing was 0.6nm;
[0033] S2, placing the bonding surface of the c-axis crystal of the lithium yttrium fluoride crystal after polishing in step S1 into a mixed solution of 3-hydroxypropyltriethoxysilane and ethanol for 2 hours, the mass ratio between 3-hydroxypropyltriethoxysilane and ethanol being 1:35, and then repeatedly washing with an excess of a mixed solution of acetone and ethanol, the mass ratio between acetone and ethanol being 1:3, and naturally drying to obtain a pre-treated c-axis crystal of lithium yttrium fluoride;
[0034] The bonding surface of the a-axis doped lithium yttrium fluoride crystal in step S1 is placed in a mixed solution of 11-carboxy undecyl triethoxysilane and ethanol for 4 hours, wherein the mass ratio of 11-carboxy undecyl triethoxysilane to ethanol is 1:30, and then repeatedly washed with an excess of a mixed solution of acetone and ethanol, wherein the mass ratio of acetone to ethanol is 1:3, and naturally dried to obtain a pre-treated a-axis doped lithium yttrium fluoride crystal;
[0035] S3, pre-bonding the pre-treated c-axis yttrium lithium fluoride crystal obtained in step S2 to the end of the pre-treated a-axis doped yttrium lithium fluoride crystal by direct bonding technology to obtain a first intermediate product;
[0036] S4, applying a pressure of 4 MPa in a direction perpendicular to the bonding surface to the first intermediate product obtained in step S3 for 3 hours to obtain a second intermediate product;
[0037] S5, hot isostatic pressing the second intermediate product obtained in step S4, the pressure of hot isostatic pressing is 30MPa, the temperature is 300°C, and the time is 6 hours, and vacuum annealing is performed after hot isostatic pressing, the pressure of vacuum annealing is 4Pa, the time is 18 hours, and the temperature is 400°C, to obtain lithium yttrium fluoride composite crystals
[0038] Example 2
[0039] The preparation method of lithium yttrium fluoride composite crystal comprises the following steps:
[0040] S1, polishing the bonding surface of the lithium yttrium fluoride crystal in the c-axis crystal direction with a polishing solution A, wherein the components of the polishing solution A include hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water, and the mass ratio of hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water is 1:2.5:8:60;
[0041] Polishing the bonding surface of the a-axis doped lithium yttrium fluoride crystal with a polishing solution B, wherein the a-axis doped lithium yttrium fluoride crystal is doped with 2at% thulium, and the components of the polishing solution B include sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, deionized water and nano vermiculite, and the mass ratio of the sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, nano vermiculite and deionized water is 1:3:2:7:80;
[0042] The smoothness of the c-axis lithium yttrium fluoride crystal and the a-axis doped lithium yttrium fluoride crystal after polishing reached 10 / 5, and the roughness of the lithium yttrium fluoride crystal and the doped lithium yttrium fluoride crystal after polishing was 0.6nm;
[0043] S2, placing the bonding surface of the c-axis crystal of the lithium yttrium fluoride crystal after polishing in step S1 into a mixed solution of 3-hydroxypropyltriethoxysilane and ethanol for 1h, the mass ratio between 3-hydroxypropyltriethoxysilane and ethanol being 1:20, and then repeatedly washing with an excess of a mixed solution of acetone and ethanol, the mass ratio between acetone and ethanol being 1:2, and naturally drying to obtain a pre-treated c-axis crystal of lithium yttrium fluoride;
[0044] The bonding surface of the a-axis doped lithium yttrium fluoride crystal in step S1 is placed in a mixed solution of 11-carboxy undecyl triethoxysilane and ethanol for 2 hours, wherein the mass ratio of 11-carboxy undecyl triethoxysilane to ethanol is 1:25, and then repeatedly washed with an excess of a mixed solution of acetone and ethanol, wherein the mass ratio of acetone to ethanol is 1:2, and naturally dried to obtain a pre-treated a-axis doped lithium yttrium fluoride crystal;
[0045] S3, pre-bonding the pre-treated c-axis yttrium lithium fluoride crystal obtained in step S2 to the end of the pre-treated a-axis doped yttrium lithium fluoride crystal by direct bonding technology to obtain a first intermediate product;
[0046] S4, applying a pressure of 1 MPa in a direction perpendicular to the bonding surface to the first intermediate product obtained in step S3 for 2 hours to obtain a second intermediate product;
[0047] S5. The second intermediate product obtained in step S4 is subjected to hot isostatic pressing treatment, wherein the pressure of the hot isostatic pressing treatment is 2 MPa, the temperature is 250° C., and the time is 2 hours. After the hot isostatic pressing treatment, vacuum annealing is performed, wherein the pressure of the vacuum annealing treatment is 0.001 Pa, the time is 2 hours, and the temperature is 300° C., to obtain lithium yttrium fluoride composite crystals.
[0048] Example 3
[0049] The preparation method of lithium yttrium fluoride composite crystal comprises the following steps:
[0050] S1, polishing the bonding surface of the lithium yttrium fluoride crystal in the c-axis crystal direction with a polishing solution A, wherein the components of the polishing solution A include hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water, and the mass ratio of hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water is 1:3:10:80;
[0051] Polishing the bonding surface of the a-axis doped lithium yttrium fluoride crystal with a polishing solution B, wherein the a-axis doped lithium yttrium fluoride crystal is doped with 3at% thulium, and the components of the polishing solution B include sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, deionized water and nano vermiculite, and the mass ratio of the sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, nano vermiculite and deionized water is 1:6:5:12:110;
[0052] The smoothness of the c-axis lithium yttrium fluoride crystal and the a-axis doped lithium yttrium fluoride crystal after polishing reached 10 / 5, and the roughness of the lithium yttrium fluoride crystal and the doped lithium yttrium fluoride crystal after polishing was 0.8nm;
[0053] S2, placing the bonding surface of the c-axis crystal of the lithium yttrium fluoride crystal after polishing in step S1 into a mixed solution of 3-hydroxypropyltriethoxysilane and ethanol for 3 hours, the mass ratio between 3-hydroxypropyltriethoxysilane and ethanol is 1:45, and then repeatedly washing with an excess of a mixed solution of acetone and ethanol, the mass ratio between acetone and ethanol is 1:5, and naturally drying to obtain a pre-treated c-axis crystal of lithium yttrium fluoride;
[0054] The bonding surface of the a-axis doped lithium yttrium fluoride crystal in step S1 is placed in a mixed solution of 11-carboxy undecyl triethoxysilane and ethanol for 2 hours, wherein the mass ratio of 11-carboxy undecyl triethoxysilane to ethanol is 1:40, and then repeatedly washed with an excess of a mixed solution of acetone and ethanol, wherein the mass ratio of acetone to ethanol is 1:5, and naturally dried to obtain a pre-treated a-axis doped lithium yttrium fluoride crystal;
[0055] S3, pre-bonding the pre-treated c-axis yttrium lithium fluoride crystal obtained in step S2 to the end of the pre-treated a-axis doped yttrium lithium fluoride crystal by direct bonding technology to obtain a first intermediate product;
[0056] S4, applying a pressure of 5 MPa in a direction perpendicular to the bonding surface to the first intermediate product obtained in step S3 for 10 hours to obtain a second intermediate product;
[0057] S5. The second intermediate product obtained in step S4 is subjected to hot isostatic pressing treatment, wherein the pressure of the hot isostatic pressing treatment is 60 MPa, the temperature is 450° C., and the time is 10 hours. After the hot isostatic pressing treatment, vacuum annealing is performed, wherein the pressure of the vacuum annealing treatment is 10 Pa, the time is 32 hours, and the temperature is 500° C., to obtain lithium yttrium fluoride composite crystals.
[0058] Example 4
[0059] The preparation method of lithium yttrium fluoride composite crystal comprises the following steps:
[0060] S1, polishing the bonding surface of the lithium yttrium fluoride crystal in the c-axis crystal direction with a polishing liquid A, wherein the components of the polishing liquid A include hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water, and the mass ratio of hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water is 1:3:6:50;
[0061] Polishing the bonding surface of the a-axis doped lithium yttrium fluoride crystal with a polishing solution B, wherein the a-axis doped lithium yttrium fluoride crystal is doped with 1at% holmium and 2at% erbium, and the components of the polishing solution B include sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, deionized water and nano vermiculite, and the mass ratio of the sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, nano vermiculite and deionized water is 1:4:3:10:90;
[0062] The smoothness of the c-axis yttrium lithium fluoride crystal and the a-axis doped yttrium lithium fluoride crystal after polishing reached 10 / 5, and the roughness of the yttrium lithium fluoride crystal and the doped yttrium lithium fluoride crystal after polishing was 0.7nm;
[0063] S2, placing the bonding surface of the c-axis crystal of the lithium yttrium fluoride crystal after polishing in step S1 into a mixed solution of 3-hydroxypropyltriethoxysilane and ethanol for 2 hours, the mass ratio between 3-hydroxypropyltriethoxysilane and ethanol being 1:30, and then repeatedly washing with an excess of a mixed solution of acetone and ethanol, the mass ratio between acetone and ethanol being 1:4, and naturally drying to obtain a pre-treated c-axis crystal of lithium yttrium fluoride;
[0064] The bonding surface of the a-axis doped lithium yttrium fluoride crystal in step S1 is placed in a mixed solution of 11-carboxy undecyl triethoxysilane and ethanol for 3 hours, wherein the mass ratio of 11-carboxy undecyl triethoxysilane to ethanol is 1:35, and then repeatedly washed with an excess of a mixed solution of acetone and ethanol, wherein the mass ratio of acetone to ethanol is 1:4, and naturally dried to obtain a pre-treated a-axis doped lithium yttrium fluoride crystal;
[0065] S3, pre-bonding the pre-treated c-axis yttrium lithium fluoride crystal obtained in step S2 to the end of the pre-treated a-axis doped yttrium lithium fluoride crystal by direct bonding technology to obtain a first intermediate product;
[0066] S4, applying a pressure of 3 MPa in a direction perpendicular to the bonding surface to the first intermediate product obtained in step S3 for 5 hours to obtain a second intermediate product;
[0067] S5. The second intermediate product obtained in step S4 is subjected to hot isostatic pressing treatment, wherein the pressure of the hot isostatic pressing treatment is 10 MPa, the temperature is 300° C., and the time is 3 hours. After the hot isostatic pressing treatment, vacuum annealing is performed, wherein the pressure of the vacuum annealing treatment is 0.1 Pa, the time is 8 hours, and the temperature is 350° C., to obtain lithium yttrium fluoride composite crystals.
[0068] Example 5
[0069] The preparation method of lithium yttrium fluoride composite crystal comprises the following steps:
[0070] S1, polishing the bonding surface of the lithium yttrium fluoride crystal in the c-axis crystal direction with a polishing liquid A, wherein the components of the polishing liquid A include hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water, and the mass ratio of hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water is 1:3:6:50;
[0071] Polishing the bonding surface of the a-axis doped lithium yttrium fluoride crystal with a polishing solution B, wherein the a-axis doped lithium yttrium fluoride crystal is doped with 1at% thulium, 1at% holmium, 1at% erbium and 1at% praseodymium, and the components of the polishing solution B include sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, deionized water and nano vermiculite, and the mass ratio of the sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, nano vermiculite and deionized water is 1:3:5:12:100;
[0072] The smoothness of the c-axis lithium yttrium fluoride crystal and the a-axis doped lithium yttrium fluoride crystal after polishing reached 10 / 5, and the roughness of the lithium yttrium fluoride crystal and the doped lithium yttrium fluoride crystal after polishing was 0.6nm;
[0073] S2, placing the bonding surface of the c-axis crystal of the lithium yttrium fluoride crystal after polishing in step S1 into a mixed solution of 3-hydroxypropyltriethoxysilane and ethanol for 3 hours, the mass ratio between 3-hydroxypropyltriethoxysilane and ethanol is 1:35, and then repeatedly washing with an excess of a mixed solution of acetone and ethanol, the mass ratio between acetone and ethanol is 1:4, and naturally drying to obtain a pre-treated c-axis crystal of lithium yttrium fluoride;
[0074] The bonding surface of the a-axis doped lithium yttrium fluoride crystal in step S1 is placed in a mixed solution of 11-carboxy undecyl triethoxysilane and ethanol for 3 hours, wherein the mass ratio of 11-carboxy undecyl triethoxysilane to ethanol is 1:35, and then repeatedly washed with an excess of a mixed solution of acetone and ethanol, wherein the mass ratio of acetone to ethanol is 1:4, and naturally dried to obtain a pre-treated a-axis doped lithium yttrium fluoride crystal;
[0075] S3, pre-bonding the pre-treated c-axis yttrium lithium fluoride crystal obtained in step S2 to the end of the pre-treated a-axis doped yttrium lithium fluoride crystal by direct bonding technology to obtain a first intermediate product;
[0076] S4, applying a pressure of 2 MPa in a direction perpendicular to the bonding surface to the first intermediate product obtained in step S3 for 7 hours to obtain a second intermediate product;
[0077] S5. The second intermediate product obtained in step S4 is subjected to hot isostatic pressing treatment, wherein the pressure of the hot isostatic pressing treatment is 30 MPa, the temperature is 350° C., and the time is 6 hours. After the hot isostatic pressing treatment, vacuum annealing is performed, wherein the pressure of the vacuum annealing treatment is 5 Pa, the time is 10 hours, and the temperature is 300° C., to obtain lithium yttrium fluoride composite crystals.
[0078] Comparative Example 1
[0079] The difference between Comparative Example 1 and Example 1 is that in step S1, ordinary abrasive-free polishing liquid is used for both the lithium yttrium fluoride crystals and the doped lithium yttrium fluoride crystals, and the main components of the ordinary abrasive-free polishing liquid are deionized water and ethanol. The remaining steps are exactly the same as in Example 1.
[0080] Comparative Example 2
[0081] The difference between Comparative Example 2 and Example 1 is that in step S1, ordinary abrasive polishing liquid is used for both the lithium yttrium fluoride crystals and the doped lithium yttrium fluoride crystals. The ordinary abrasive polishing liquid is composed of additives such as silicon dioxide, sodium phosphate, aluminum nitrate and deionized water, and the remaining steps are exactly the same as in Example 1.
[0082] Comparative Example 3
[0083] The difference between Comparative Example 3 and Example 1 is that step S2 is omitted. After polishing the lithium yttrium fluoride crystal and the doped lithium yttrium fluoride crystal respectively in step S1, they are directly cleaned and dried, and the remaining steps are exactly the same as in Example 1.
[0084] Comparative Example 4
[0085] The difference between Comparative Example 4 and Comparative Example 3 is that not only step S2 is omitted, but also in step S1, both the lithium yttrium fluoride crystal and the doped lithium yttrium fluoride crystal are polished using ordinary abrasive polishing liquid, and the remaining steps are exactly the same as those in Example 1.
[0086] Comparative Example 5
[0087] Comparative Example 5 is a lithium yttrium fluoride composite crystal prepared by the preparation method in Example 1 of Publication No. CN104099665B.
[0088] Ten groups of lithium yttrium fluoride composite crystals were prepared through the above Examples 1-5 and Comparative Examples 1-5, and the unit area interface strength (kg / cm 2 ) and interface damage threshold (J / cm 2 ) was tested, and the test results are shown in Table 1 below:
[0089] Table 1: Test table of unit area interface strength and interface damage threshold of lithium yttrium fluoride composite crystals prepared in Examples 1-5 and Comparative Examples 1-5
[0090] <![CDATA[Interface strength per unit area (kg / cm 2 )]]> <![CDATA[Interface damage threshold (J / cm 2 )]]> Example 1 45 32 Example 2 36 27 Example 3 44 32 Example 4 48 35 Example 5 45 33 Comparative Example 1 40 25 Comparative Example 2 36 28 Comparative Example 3 32 23 Comparative Example 4 29 18 Comparative Example 5 36 22
[0091] It can be seen from the data of Example 1 and Comparative Examples 1-4 in Table 1 above that the interface strength per unit area and the interface damage threshold of the lithium yttrium fluoride composite crystals are reduced by changing the composition of the polishing liquid or canceling the crystal immersion in step S2, which proves that the bonding interface strength of the lithium yttrium fluoride composite crystals prepared by the present application can be effectively improved. At the same time, the interface strength per unit area and the interface damage threshold of the lithium yttrium fluoride composite crystals prepared in Examples 1-5 of the present invention are also effectively improved relative to the lithium yttrium fluoride composite crystals prepared in Example 1 of CN104099665B.
[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing lithium yttrium fluoride composite crystals, characterized in that: The steps include: S1, polishing the bonding surface of the lithium yttrium fluoride crystal in the c-axis crystal direction with polishing liquid A, and polishing the bonding surface of the doped lithium yttrium fluoride crystal in the a-axis crystal direction with polishing liquid B; S2, placing the bonding surface of the c-axis crystal of the yttrium fluoride lithium crystal after polishing in step S1 into a mixed solution of 3-hydroxypropyltriethoxysilane and ethanol for 1-3 hours, then repeatedly washing with an excess of organic solvent, and naturally drying to obtain a pre-treated c-axis crystal of yttrium fluoride lithium crystal; placing the bonding surface of the a-axis crystal of the doped yttrium fluoride lithium crystal in step S1 into a mixed solution of 11-carboxy undecyltriethoxysilane and ethanol for 2-5 hours, then repeatedly washing with an excess of organic solvent, and naturally drying to obtain a pre-treated a-axis crystal of doped yttrium fluoride lithium crystal; S3, pre-bonding the pre-treated c-axis yttrium lithium fluoride crystal obtained in step S2 to the end of the pre-treated a-axis doped yttrium lithium fluoride crystal by direct bonding technology to obtain a first intermediate product; S4, applying a pressure of 1-5 MPa in a direction perpendicular to the bonding surface to the first intermediate product obtained in step S3 for 2-10 hours to obtain a second intermediate product; S5. The second intermediate product obtained in step S4 is subjected to hot isostatic pressing treatment, wherein the pressure of the hot isostatic pressing treatment is 2-60 MPa, the temperature is 250-450° C., and the time is 2-10 hours. After the hot isostatic pressing treatment, vacuum annealing is performed, and the pressure of the vacuum annealing is 0.001-10 Pa, the time is 2-32 hours, and the temperature is 300-500° C. to obtain lithium yttrium fluoride composite crystals.
2. The method for preparing lithium yttrium fluoride composite crystal according to claim 1, characterized in that: The a-axis doped lithium yttrium fluoride crystal is doped with a rare earth element, and the rare earth element is selected from at least one of thulium, holmium, erbium and praseodymium.
3. A laser crystal bonding method according to claim 1, characterized in that: The components of the polishing liquid A in step S1 include hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water, and the mass ratio of hexadecylammonium bromide, ammonium fluoride, nano-silicon dioxide and deionized water is 1:(2-3):(4-10):(40-80).
4. A laser crystal bonding method according to claim 1, characterized in that: The components of the polishing liquid B in step S1 include sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, deionized water and nano vermiculite, and the mass ratio of sodium dodecyl sulfate, 68wt% nitric acid, 98wt% sulfuric acid, nano vermiculite and deionized water is 1:(3-6):(2-5):(7-12):(80-110).
5. The laser crystal bonding method according to claim 1, characterized in that: In the step S1, the smoothness of the c-axis lithium yttrium fluoride crystal and the a-axis doped lithium yttrium fluoride crystal after polishing both reaches 10 / 5, and the roughness of the lithium yttrium fluoride crystal and the doped lithium yttrium fluoride crystal after polishing is not greater than 0.8nm.
6. The laser crystal bonding method according to claim 1, characterized in that: The organic solvent in step S2 is a mixture of ethanol and acetone, and the mass ratio of acetone to ethanol is 1:(2-5).
7. The laser crystal bonding method according to claim 1, characterized in that: The mass ratio between 3-hydroxypropyltriethoxysilane and ethanol in step S2 is 1:(20-45).
8. The laser crystal bonding method according to claim 1, characterized in that: The mass ratio between 11-carboxyundecyltriethoxysilane and ethanol in step S2 is 1:(25-40).
9. A lithium yttrium fluoride crystal, characterized in that: The crystal is prepared by the method for preparing lithium yttrium fluoride composite crystals as described in any one of claims 1 to 8.
Citation Information
Patent Citations
A kind of yttrium-lithium fluoride composite crystal and preparation method thereof
CN104099665B
Yttrium lithium fluoride composite crystal and preparation method thereof
CN104099665A
Yttrium aluminate composite crystal and preparation method thereof
CN106087055A
Device structure of cadmium zinc telluride detector and preparation process thereof
CN112349797A
Preparation method of composite laser crystal
CN112795987A